2020
DOI: 10.3389/fonc.2020.00715
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Extrathoracic Metastases in Different Histological Types of Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths mainly attributable to metastasis, especially extrathoracic metastasis. This large-cohort research is aimed to explore metastatic profiles in different histological types of lung cancer, as well as to assess clinicopathological and survival significance of diverse metastatic lesions. Lung cancer cases were extracted and enrolled from the Surveillance, Epidemiology, and End Results (SEER) database. χ 2 -tests were conducted to make comparisons of metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 23 publications
6
39
2
Order By: Relevance
“…Next, in order to assess the clinical relevance of metastasis pattern in SCLC, we investigated the timing and co‐occurrence of organ metastases. With regards to the incidence of distant metastases, the most common metastatic sites were the liver, brain, bone, and adrenal glands, which is in line with the findings of others 5,10,25 . Importantly, we also found that the onset of bone, brain, and pericardial metastases tended to be late, whereas the development of adrenal gland and liver metastases were usually early events during SCLC progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Next, in order to assess the clinical relevance of metastasis pattern in SCLC, we investigated the timing and co‐occurrence of organ metastases. With regards to the incidence of distant metastases, the most common metastatic sites were the liver, brain, bone, and adrenal glands, which is in line with the findings of others 5,10,25 . Importantly, we also found that the onset of bone, brain, and pericardial metastases tended to be late, whereas the development of adrenal gland and liver metastases were usually early events during SCLC progression.…”
Section: Discussionsupporting
confidence: 92%
“…Our group previously found that in lung adenocarcinoma patients bone metastases tend to appear together with adrenal gland and liver metastases, while pleural and pericardial, and skin and adrenal gland metastasis pairs also appear more frequently together than expected if metastatic events occurred independently 9 . Of note, a very recent large population‐based study on unselected Asian lung cancer patients also suggested that bone metastases tended to onset together with liver metastases 10 . To date, however, no metastasis pattern‐specific analyses have been conducted in Caucasian SCLC patients.…”
Section: Introductionmentioning
confidence: 83%
“…Similarly, Bianchi et al 13 found a higher bone metastasis rate than to lung and liver for bladder cancer with distant metastasis. Histology types are associated with the metastasis pattern in lung cancer; 23 however, studies about the relationship between histology types and metastatic pattern are deficient for bladder cancer. Our research suggested that the metastasis pattern depended on histology type.…”
Section: Discussionmentioning
confidence: 99%
“…Small cell lung cancer tumors commonly metastasize to the brain, liver, bones, and distant lymph nodes, but also metastasize at lower frequencies in many other organs (Froudarakis, 2012; Nakazawa et al , 2012; Ryu et al , 2016; Bütof et al , 2017; Wang et al , 2020a) (Fig 1). Little is known about the molecular and cellular mechanisms that allow SCLC cells to home to, seed, and grow into micro‐ and macro‐metastases in specific organ environments.…”
Section: Introductionmentioning
confidence: 99%